P442 Serum vedolizumab trough levels are associated with remission rate but not with extra-intestinal manifestations in IBD patients. (27th May 2021) - Tzadok, R; Fliss-Isakov, N; Aviv Cohen, N; Ron, Y; Maharshak, N; Hirsch, A
Abstract: Background: The correlation between vedolizumab trough levels and inflammatory bowel diseases (IBD) remission rates has not yet been fully defined. We aimed to evaluate the association between vedolizumab serum trough levels and disease clinical and extra-intestinal manifestations (EIMs) and biomarker activity in IBD patients. Methods: Forty-six patients (31 ulcerative colitis, 15 Crohn's disease) who started vedolizumab therapy were retrospectively followed. Clinical and laboratory data were collected before treatment, during induction and maintenance until week 52 from initiation. Documentation of EIMs included peripheral and axial arthropathy, cutaneous and ocular manifestations and perianal disease. Clinical remission was defined as a Harvey-Bradshaw Index (HBI)<5 or a Simple Clinical Colitis Activity Index (SCCAI)<3. Biomarker normalization was defined as C-reactive protein level<5 mg/L and fecal calprotectin level<250 µg/g. Two-sample t-tests were used to find correlations between drug levels and disease activity. Results: Higher week-2 trough serum vedolizumab levels were associated with week 14 clinical remission compared to patients with an active disease (30.55±2.22 µg/ml vs 22.28±3.57µg/ml, p=0.05) and with weeks-14 and -30 biomarker normalization (33.77±2.98 µg/ml vs 23.6±3.19 µg/ml, p=0.05 and 30.33±1.95 µg/ml vs 19.66±6.83 µg/ml, p=0.05, respectively). Week-6 vedolizumab levels were associated with week-30 clinical remission (30.52±3.48 µg/ml vs 15.35±4.94 µg/ml, p=0.03) and biomarker normalization (28.44±2.36 µg/ml vs 15.76±4.87µg/ml, p=0.02), and week 14 vedolizumab levels were associated week 30 biomarker normalization (14.81±1.64 µg/ml vs 6.23±2.25 µg/ml, p=0.03). Throughout the follow-up period, 24% of patients presented with EIMs (n=11). No association was found between vedolizumab levels and endoscopic outcomes or EIMs activity. Conclusion: Trough serum vedolizumab levels at induction is associated with remission induction and maintenance but not with EIMs improvement. Assessment of early vedolizumab trough levels may be considered for prediction of response to therapy.